Fabric membranes as Daylighting Control Systems in buildings - Mundo Hernandez, Julia Judith (2006)
The latter half of the 20th century saw the development of lightweight tensioned translucent membranes as shading devices and their increasing use in providing daylight and daylight control. Buildings with high lighting consumption and long operation hours in particular are including translucent membranes in their daylighting strategies. For this reason, the use of reliable tools for the prediction of the lighting environment experienced in daylit spaces, which exploit translucent membranes, has become essential. To date most analytic efforts related to predicting daylighting performance has concentrated on the analysis of light penetration through glass openings. Little attention has been paid to the light transmission through fabric membranes. The membranes itself are normally in tensioned creating double curvature shapes. The simulation of light transmitted through membranes involves the modelling of complex geometries, which places significant demand to their modelling. This thesis explores the daylighting performance of sports buildings that include translucent membranes as part of their daylighting strategy. Performance of these buildings has been assessed by field illuminance measurements, physical scale modelling in artificial sky and three-dimensional modelling using Radiance software. The accuracy of the simulation tools is assessed against the lighting data recorded in the field study. Findings show that physical scale models tend to overestimate the illuminance levels and daylight factors of the sports halls. On the other hand, Radiance simulations proved to be accurate in terms of daylight factors and illuminance distribution in the playing areas. Finally, a questionnaire has been distributed among the occupants of the three case study buildings and one totally artificially illuminated sports centre. The purpose of this survey is to evaluate the users satisfaction towards the lighting environment of the enclosures. The ability to accurately predict the daylighting performance in membrane sports buildings is significant for the development of research in daylighting and sustainable architecture. In addition, the further use of translucent membranes for the control of natural light in all type of buildings relies on the possibility to confidently predict their daylighting performance.